Current Communication Technologies in the Promotion of Scientific Knowledge - Vladimirovich Klyuev, Yuriy; Evgenievna Vinogradova, Ksenia; Valerievna Zubko, Daria; Yakovlevich Misonzhnikov, Boris; Sergeevna Melnik, Galina (International Journal of Engineering and Technology, 2018)
Exchange of scientific information is a basic component within the process of promoting humanitarian, life-science and technical knowledge. Distortions and disruptions in providing tactical and strategic mass- and corporative communication have a negative impact on transferring and receiving specialized information, both within the corresponding information system, and beyond its limits. Development of a structure of specialized communications of the scientific communities depends on a significant factor: the dialogue is conducted between the subjects of a certain field of scientific knowledge or within a certain research institution. To a certain extent, subjects of scientific communication play their part in providing scientific communication flows, which facilitates the development of scientific ideas about the reality within a scientific corporation, as well as outside it. Communications among the members of the scientific communities can be organized at the global, international or national level, or locally, within a certain research organization. Present article focused on the current communication technologies that were used for promoting scientific knowledge. It addressed the principles, characteristics and functions of communicative activity in the field of science and higher education, which defined the state and development perspective of the social progress.Â